Technology Enhanced Communicative Lesson Design for Islamic EFL Curriculum Integration - Hafizatun Septi Arizky; Mardiyah Arizky; Masda Egy Faradilla; Adelia Salsabilla; Aisha Farhana; Hesty Widiastuty (Al-Mudarris, 2026)
English instruction in Islamic educational institutions navigates a fundamental tension: it must deliver genuine communicative competence while remaining anchored in the moral and spiritual purposes of Islamic education (tarbiyah). This article addresses that tension by proposing Technology-Enhanced Communicative Lesson Design (TECLD), a pedagogical planning framework that integrates digital pedagogy, communicative language teaching (CLT), and Islamic curriculum values into a unified lesson structure. Drawing on a systematic qualitative literature review of 21 peer-reviewed sources published between 2017 and 2025, the discussion examines how technology-mediated communicative activities can be aligned with the tarbiyah ideal of holistic learner development encompassing intellectual, moral, social, and spiritual dimensions. The central argument is that technology should serve not merely as an engagement tool or score-lifting mechanism but as a medium for meaningful communication that cultivates Islamic ethical dispositions: honesty (amanah), courtesy (adab), cooperation (taʻawun), accountability (masʺuliyyah), and self-development (tazakkiy). Communicative competence, reconceptualised through an Islamic lens, extends beyond fluency and accuracy to encompass ethical speech and appropriate conduct across digital, social, and intercultural contexts. Digital instruments including collaborative documents, video-based tasks, online discussion forums, and AI-assisted writing tools can support activities such as digital storytelling, group debate, reflective journaling, and project-based learning. The article concludes that TECLD acquires full pedagogical and moral legitimacy within Islamic EFL classrooms only when its learning objectives, materials, tasks, and assessment instruments are deliberately aligned with both communicative language goals and the character formation aims of the Islamic curriculum.